Application of waste banana peels for wastewater treatment: a review - Huzaisham, Nur Athirah; Marsi, Noraini; Muhd Rus, Anika Zafiah; Masrol, Shaiful Rizal; Mahmood, Salwa; Main, Nor Mazlana; Mohd Fodzi, Muhammad Haikal; Thana Singam, Rupashinii (American Scientific Publishers, 2020)
This review paper focuses on the use of recycled banana peels for wastewater treatment. In India, more than 57.6 million tonnes of banana waste peels were produced each year, majorly are used as adsorbents to remove contaminants and pollutants that exist in the wastewater like heavy ions, organic and inorganic pollutants. To date, the use of waste banana peels as adsorbents have obtained substantial attention and countless modification have been done in order to improve their adsorption characteristics. Based on literature survey regarding the abundance of waste banana peels around the world, they are conceived to have considerable absorbency with optimistic appli-cation toward pollutants. According to published articles from the past 20 years, the technique of adsorption was recognized as most exceptional and cost-saving methods of treating wastewater with adsorption rate up to 98% of heavy metal ions removal and up to 98.93% for organic and inorganic compounds removal. Adsorption is most frequently used to remove atoms, molecules or ions from drinking water preparation, groundwater or as tertiary cleaning such as purification of bio-logical water and wastewater treatment. Adsorption occurs when molecules in a liquid attach to the surface of a solid substance. This review extends applicable literature on the application of waste banana peels and its properties as an adsorbent on removing various pollutants in the wastewa-ter. Evidently, adsorbents derived from waste banana peels demonstrated remarkable effectiveness towards removing various pollutants where the adsorption rate increases as the adsorbent dosage increases. Results concerning waste banana peels as adsorbents from several published articles have been discussed elaborately along with the future research perspective on waste banana peels.